SOCIAL AND HISTORIC DETERMINATION OF THE TRANSLATORS’ DECISIONS (BY THE EXAMPLE OF UKRAINIAN TRANSLATIONS OF CREATIVES E. HEMINGWAY’S OF DIFFERENT TIMES) - Romanenko, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper considers the influence of social and historic factors on the process of Ukrainian translation of E. Hemingway’s literary works within soviet times and periods of independence. The research reveals the analogues in the translators’ strategies and proves the potential of the translation in the antagonism towards ideology and linguicide.